2019
DOI: 10.18502/npt.v6i3.1255
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Persian version of the confusion assessment method for intensive care units

Abstract: Background & Aim: Delirium is prevalent in the intensive care unit, especially among mechanically-ventilated patients. Delirium is associated with a significant increase in adverse outcomes but it usually remains undiagnosed, making it necessary to develop and validate diagnostic tools. This study determined the validity and reliability of the Persian version of the Confusion Assessment Method for Intensive Care Units in Iran. Methods & Materials: This cross-sectional study was conducted in open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…A total of 96 patients were included in the study and were divided into a group receiving intravenous thiamine 200 mg/day and a group receiving intravenous 0.9% saline solution for three days. The validated Persian version of the CAM-ICU was used to assess delirium, and the level of sedation was measured using the RASS scale, every 12 h [38]. The outcome showed that the incidence of delirium was significantly lower in the thiamine group than in the placebo group.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 96 patients were included in the study and were divided into a group receiving intravenous thiamine 200 mg/day and a group receiving intravenous 0.9% saline solution for three days. The validated Persian version of the CAM-ICU was used to assess delirium, and the level of sedation was measured using the RASS scale, every 12 h [38]. The outcome showed that the incidence of delirium was significantly lower in the thiamine group than in the placebo group.…”
Section: Resultsmentioning
confidence: 99%
“…Adinehvand et al ( 10 ) obtained a correlation coefficient of 0.86 by the test-retest method for the GCS scale in Iran. Also, Arbabi et al ( 26 ) obtained a Cronbach alpha coefficient of 0.84 for the BPS scale.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Fig. 1 , patients were evaluated once daily for delirium: at first, the level of consciousness was measured by The Richmond Agitation Sedation Scale (RASS) and - a RASS score of − 5 or − 4 is considered coma- if it exceeds − 4 (− 3 to + 4) then the confusion assessment method (CAM) questionnaire [ 22 , 23 ] and the General Practitioner Assessment of Cognition (GPCOG) test was employed; GPCOG test was carried out on the first evaluation only, while RASS and CAM were performed on a daily basis until the patient was discharged or developed delirium. Initially, the researchers evaluated all patients thoroughly, and bedside nurses who had both RASS and CAM training conducted routine evaluations every day until the patients were discharged or developed delirium.…”
Section: Methodsmentioning
confidence: 99%